Pédagogie de la créativité : de l'émotion à l'apprentissage - Isabelle Puozzo
Creativity has become a fashionable term used in several domains, in particular the professional, technological, economic, social ones, but not exclusively. The school doesn't escape this contagion. The sociocognitive theory (Bandura, 1997/2007) and the approche multivariée (« multivariate approach ») (Lubart, 2003) present theories which allow us to consider learning in a holistic and interdependent way where the cognitive dimension crosses the emotional, physiological and environmental ones through the elaboration of a creative device. Contrary to popular belief though (Craft, 2005; Robinson, 2011), creativity is not limited to the creation of products, but it is primarily a set of multiple processes. Moving from some empirical research data, this article provides some elements of analysis of the emotional process which takes place within the implementation of a creative device and presents some theoretical basis to develop a pedagogy of creativity in the language class in view of developing a translanguaging paradigm.